(untitled) (Bangladesh Journal of Medical Education, 2026)
Background: English is the predominant language in medical curriculum in the world, including in Bangladesh. Bangladeshi medical undergraduates, who were predominantly taught in Bangla throughout their prior education, appear to encounter significant challenges in understanding the English language used in Anatomy. Objective: The study aimed to analyze Bangladeshi medical undergraduates’ perceptions, experiences, and views regarding difficulties faced in understanding English-in-Anatomy. Methods: The study was descriptive cross-sectional. A questionnaire-survey was conducted among 278 first year medical undergraduates. Descriptive statistics were used to analyze the data. Results: The survey revealed that about one-third of these students faced difficulties in understanding the English of Anatomy textbooks. About 40-50% of undergraduates faced either ’huge’ or ’considerable’ difficulty in understanding the meaning of words, the meaning of sentences and the text’s overall meaning. About 60% felt that a lack of proper understanding of basic grammar did not impede their understanding of English in Anatomy, and 80% believed that their weakness was due to the Bangla medium of their earlier study. The nature, types of difficulties, and perceived reasons were outlined. Conclusion: Further studies should be continued to give the finding a more complete, comprehensive and representative stature. BJME: Vol.-17, Issue-02, July, 2026: 12-22